Orientation-resolved attosecond photoionization delays in the N_{2}O molecule - Celso M. González-Collado; Laura Cattaneo; Etienne Plésiat; Juan J. Omiste; Jannie Vos; Jesús González-Vázquez; Piero Decleva; Ursula Keller; Alicia Palacios; Fernando Martín (Physical Review Research)
We present a thorough theoretical and experimental investigation of photoionization time delays in the N_{2}O molecule. Our theory provides actual XUV+IR time-resolved photoelectron spectra as measured in real reconstruction of attosecond beating by interference of two-photon transitions (RABBIT) experiments. This requires not only accounting for the interaction between the XUV field and the neutral molecule, but also between the IR field and the ejected electron, which is only possible through explicit evaluation of a large number of dipole couplings between molecular electronic continuum states. To compare with the results of these calculations we have performed RABBIT experiments in which the ejected electron and the resulting ionic fragments are measured in coincidence, thus allowing us to obtain photoionization delays for a particular orientation of the molecule with respect to the polarization of the XUV and IR fields. We have found very good agreement between calculated and measured RABBIT spectra for both nondissociative and dissociative ionization channels. In particular, we unambiguously show a photoionization delay of about 60 as in the vicinity of a well-known shape resonance of N_{2}O in the nondissociative ionization channel. More importantly, we show a dramatic effect of the IR field in the orientation-resolved ionization delays in the whole photon energy range investigated in this paper (18–40 eV), even at the level of relative ionization delays (i.e., delays referred to an internal reference delay) where the effect of the IR field is generally assumed to cancel out. Finally, we explicitly show that the problem of spectral congestion inherent to most molecular systems, which usually prevents extraction of photoionization delays, is substantially alleviated by resolving the molecular orientation or, ideally, by resolving both the molecular orientation and the electron emission angle, where access to perfectly isolated ionization channels is possible at specific angles.